2007
DOI: 10.1007/s10103-007-0449-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of low-level laser therapy during orthodontic movement: a preliminary study

Abstract: It has been emphasized that one of the most valuable treatment objectives in dental practice is to afford the patient a pain-free treatment. By the evolution of the laser applications, the dental committee aimed to achieve this goal without analgesic drugs and painful methods. Orthodontic treatment is one of these concerns, that one of the major components of patient to reject this treatment is the pain accompanied during the different treatment phases. Another great concern of the patient is not to get throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
201
3
69

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(287 citation statements)
references
References 38 publications
14
201
3
69
Order By: Relevance
“…Although on day 5 not in a statistically significant way, but if is clinically important to begin understanding with a different gaze the interpretation of the biology of tooth movement different from the pressure -tension theory described over 100 years ago (Sun et al, 2001) and based on animal studies (Uebelhart et al, 1990;Tortamano et al, 2009;Sygouros & Acar, 2013) at present these types of studies are not included on the evidence scale or are classified below expert opinion (Yamaguchi et al, 2007;Viecilli et al, 2008;Youssef et al, 2008;Yamaguchi et al, 2010) and this theory has begun to be revalued (Zhu et al, 2002) but it needs contemporary methods to be totally based on human.…”
Section: Discussionmentioning
confidence: 99%
“…Although on day 5 not in a statistically significant way, but if is clinically important to begin understanding with a different gaze the interpretation of the biology of tooth movement different from the pressure -tension theory described over 100 years ago (Sun et al, 2001) and based on animal studies (Uebelhart et al, 1990;Tortamano et al, 2009;Sygouros & Acar, 2013) at present these types of studies are not included on the evidence scale or are classified below expert opinion (Yamaguchi et al, 2007;Viecilli et al, 2008;Youssef et al, 2008;Yamaguchi et al, 2010) and this theory has begun to be revalued (Zhu et al, 2002) but it needs contemporary methods to be totally based on human.…”
Section: Discussionmentioning
confidence: 99%
“…2 In spite of these advantages, studies on low-level laser have shown contradictory findings. Although some studies showed an increase in osteoclastic activity or tooth movement with low-level laser, [3][4][5] others found no differences between irradiated and nonirradiated groups, 6,7 and some concluded that the speed of tooth movement decreased in lased compared with nonlased samples. 8 Because of the aforementioned divergent results, the aim of this study was to analyze the influence of low-level laser application on osteoclastic and osteoblastic activities and on degree of bone neoformation during induced tooth movement in Wistar rats.…”
Section: Introductionmentioning
confidence: 99%
“…1,3,4,5,[7][8][9][10][11][12][14][15][16][17][18]20,[23][24][25][26] We describe four fundamental points for experimental models to ensure that the evaluation of the effects of medication and phototherapy on induced tooth movement and associated root resorption is free of external influence.…”
Section: Palavras-chavementioning
confidence: 99%